The organisational activity of young people from Cieszyn Silesia (Polish-Czech borderland)[1] - Dyczek, Berenika (The journal of contemporary issues in business and government, 2021)
The article aims to present the elements of the social capital of young people living in Cieszyn Silesia. For this purpose, the author exploits Znaniecki’s concept of expansive aspirations for independence and Putnam’s concept of bridging capital (bridging capital).The study was conducted from October 2012 to January 2013 in Cieszyn Silesia, in schools located in Cieszyn, Skoczów, Ustroń and Istebna.